2003
DOI: 10.1074/jbc.m304608200
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Reverse Transcriptase, Nucleocapsid Protein, and Template Structure in the Two-step Transfer Mechanism in Retroviral Recombination

Abstract: Template switching during reverse transcription promotes recombination in retroviruses. Efficient switches have been measured in vitro on hairpin-containing RNA templates by a two-step mechanism. Pausing of the reverse transcriptase (RT) at the hairpin base allowed enhanced cleavage of the initial donor RNA template, exposing regions of the cDNA and allowing the acceptor to base pair with the cDNA. This defines the first or docking step. The primer continued synthesis on the donor, transferring or locking in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
107
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(111 citation statements)
references
References 94 publications
(91 reference statements)
4
107
0
Order By: Relevance
“…Together, these control reactions indicated that the greater RNase H cleavage observed upon addition of NC could be attributed almost entirely to improved annealing of substrates, rather than enhancement of RT RNase H activity, per se. Other studies from our laboratory have demonstrated similar enhancements of template cleavage with the addition of NC (27,31), however, without the extension and cleavage controls employed here it was difficult to distinguish between the two possible scenarios that could explain these effects. Given the data presented here, we suggest that much of the improved RNase H cleavage observed with NC in vitro is the result of improved annealing rather than a direct enhancement of RT RNase H activity by NC.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Together, these control reactions indicated that the greater RNase H cleavage observed upon addition of NC could be attributed almost entirely to improved annealing of substrates, rather than enhancement of RT RNase H activity, per se. Other studies from our laboratory have demonstrated similar enhancements of template cleavage with the addition of NC (27,31), however, without the extension and cleavage controls employed here it was difficult to distinguish between the two possible scenarios that could explain these effects. Given the data presented here, we suggest that much of the improved RNase H cleavage observed with NC in vitro is the result of improved annealing rather than a direct enhancement of RT RNase H activity by NC.…”
Section: Discussionmentioning
confidence: 72%
“…Materials-RT was purified as described (27,56) except that p66 and p51 subunits were purified separately and mixed in equal amounts prior to dialysis. DNA oligonucleotides and RNA templates T2 and T3 were obtained from Integrated DNA Technologies (Coralville, IA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, only 17.12% of the transfer events were located in the gag region in the absence of NC. It should also be noted that NC was not observed to substantially redistribute the general location of transfers with many substrates or alter the general mechanisms of strand transfer (51,52). In addition, we have reported previously a 3.8-fold decrease in the number of the transfer events in the gag hotspot site when the G-runs involved in G-quartet formation were disrupted.…”
Section: Discussionmentioning
confidence: 98%